Identificação do GBV-C nos compartimentos hepático e linfocitário em pacientes HIV-1 soropositivos co-infectados pelo vírus da Hepatite C - Barbosa, Aline de Jesus [UNIFESP] (2008)
Introduction: GBV-C is a flavivirus closely related to the hepatitis C virus. Differing from HCV, GBV-C it does not seem to be hepatotropic nor causes acute or chronic hepatitis. Because of the similar routes of transmission, HIV-GBV-C co-infection is extremely common; besides, studies demonstrated that GBV-C viremia has a beneficial effect upon HIV disease progression and mortality. Purpose: The aim of this study was to identify the compartments infected by the GBV-C in HIV seropositive patients coinfected with HCV and to correlate these infection markers with laboratorial parameters and histological findings in the triple infection. Methods: HIV-HCV co-infected patients undergoing to liver biopsy at the Hospital São Paulo were included in the study from May 2006 to May 2007. Demographic data was collected at the inclusion. Plasma samples were tested for antibodies to E2 of GBV-C by ELISA and for GBV-C RNA detection by real time PCR. Blood samples were collected to evaluate CD4 and CD8 Tcell counts, HIV, HCV and GBV-C viral loads. Biopsy specimens were stained using hematoxilin-eosin and Masson’s trichrome. Analysis of the staging, peri-portal and parenchymatous activities were adopted according to the semiquantitation criterion recommended in the National Consensus for Classification of Chronic Hepatitis. RTPCR in situ and Indirect Immunofluorescence (IFI) techniques were developed in house in order to identify possible GBV-C infected compartments. Results: A total of 20 HIVHCV co-infected patients with the mean age of 43.0 (6.2), 55% (11/20) were male, 40% (8/20) were parenterally exposed. 30% (6/20) were positive to one of the GBV-C markers, of them, 15% (3/20) were E2 positive and 15% (3/20) were positive to GBV-C RNA, indicating active viral replication. Detection of GBV-C RNA by RT-PCR in situ was compromised by the pre-analytic process of samples whereas the IFI in house was difficult to interpret because of the inespecificity of the monoclonal antibody used. HIV and GBV-C viral load correlation was not observed in this study, probably as a consequence of the reduced number of patients included. Conclusions: Triple infected patients presented lower inflammation degree, lower hepatic-histological commitment and lower HCV viral load, when compared with HIV-HCV co-infected patients GBV-C no viremic.